The Effect of Financial Distress, Auditor Switching, Audit Committee and Covid-19 Pandemic on Audit Delay - Sihombing, Tanggor; Aldanny, Shahnaz Nabiilah Zalfaa (Proceeding of International Conference on Entrepreneurship (IConEnt), 2023)
Financial reports are a source of information that can be used for decision-making, so it is necessary to carry out an audit process to assess the fairness or feasibility of presenting the financial statements prepared by the company. This study aims to prove the factors that influence audit delay. The factors tested in this study were financial distress, auditor switching, audit committees, and the COVID-19 pandemic on audit delay. This research was conducted on real estate companies listed on the Indonesia Stock Exchange for the 2018-2021 period. The number of samples in this study was 58 companies using a purposive sampling technique. Data analysis was carried out with classical assumptions and hypothesis testing using the multiple linear regression method with STATA version 17. Based on the results of the analysis it is known that audit delay is not affected by financial distress, auditor switching, and audit committee while audit delay is positively affected by the COVID-19 pandemic.